"Slow Down! Your Loved One Is Waiting For You 2.0": E-Book for motorcyclists / Farzana Izzati Abdullah ... [et al.] - Abdullah, Farzana Izzati; Ahmad, Yarina; Bakar, Ahmad Naqiyuddin; Jaafar, Harlina Suzana (2021)
The reality of road traffic crashes is known as a long-standing issue in many countries around the world and Malaysia is not an exception. This issue is increasing due to the lack of strict regulation from higher authorities and three main contributing factors contribute to road traffic crashes (1) human factor; (2) road condition; and (3) vehicle condition. In Malaysia, the number of deaths in road traffic crashes for motorcyclists is the highest compared to the other types of vehicles. Thus, this product aims to create awareness of road safety among motorcyclists and provide a guideline by giving an e-book to the motorcyclists once they completed their motorcycle riding test at the driving school. The uniqueness of this e-book needs the motorcyclists to scan QR codes thru their mobile phones that will link to this product. As we live in a sophisticated world and heading towards saving the environment, this product is very convenient and accessible to motorcyclists to use. Besides, this e-book can be brought easily wherever motorcyclists go. The novelty of this product act as a new approach for the government to promote road safety and reducing the number of road traffic crashes by creating awareness among motorcyclists once they completed their riding test at the driving school. The main benefit of this study is for the motorcyclists as they will receive guidelines to reduce the number of road traffic crashes in Malaysia. This product does not only help in reducing the number of road traffic crashes in Malaysia but also supports the governments intends to reduce half of the number of road traffic crashes. It is argued that reducing the number of road traffic crashes can contribute to the increasing number of the Malaysian economy.